(untitled) (Archaeologia Adriatica, 2022)
Continuous work on the archaeological topography of Korčula has recently resulted in locating an Iron Age settlement at the site of Brdo-Stine in Žrnovo at the eastern end of the island. Repeated field surveys of the site resulted in broad determination of its spatial extent, basic organizational components, as well as the character of small finds, testifying to its exceptional archaeological potential. On the basis of the position of the settlement and typo-chronological determination of the collected finds of metal (iron slag), stone (whetstones, millstones, stone anvils) and ceramic (roof tiles, molds,?, amphorae and pithoi), the settlement was preliminary dated to the Late Iron Age/Hellenistic period of an area characterized by very intense overlaying of the indigenous and Hellenistic-Roman components.